Age-Related Mitochondrial Changes after Traumatic Brain Injury - Gilmer, Lesley K. (Mary Ann Liebert, Inc., 2010)
Mitochondrial dysfunction is known to occur following traumatic brain injury (TBI) and has been well characterized. This study assessed possible age-related changes in the cortical mitochondrial bioenergetics following TBI. Three hours following a moderate TBI, tissue from the ipsilateral hemisphere (site of impact and penumbra) and the corresponding contralateral region were harvested from young (3- to 5-month-old) and aged (22- to 24-month-old) Fischer 344 rats. Synaptic and extrasynaptic mitochondria were isolated using a Ficoll gradient, and several bioenergetic parameters were examined using a Clark-type electrode. Injury-related respiration deficits were observed in both young and aged rats. Synaptic mitochondria showed an age-related decline in the rate of ATP production, and a decline in respiratory control ratios (RCR), which were not apparent in the extrasynaptic fraction. Following respiration analysis, mitochondrial samples were probed for oxidative damage (3-nitrotyrosine [3-NT], 4-hydroxynonenal [4-HNE], and protein carbonyls [PC]). All markers of oxidative damage were elevated with injury and age in the synaptic fraction, but only with injury in the extrasynaptic fraction. Synaptic mitochondria displayed the highest levels of oxidative damage and may contribute to the synaptic bioenergetic deficits seen following injury. Data indicate that cortical synaptic mitochondria appear to have an increased susceptibility to perturbation with age, suggesting that the increased mitochondrial dysfunction observed following injury may impede recovery in aged animals.